2016
DOI: 10.1177/1369433216677122
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and finite element analysis of energy dissipating outriggers

Abstract: The outriggers are widely adopted in tall and super-tall buildings. Their energy dissipation capacity can significantly influence the nonlinear seismic responses of the entire building structure. Based on an actual tall building project, the structural responses and energy dissipation capacities of three different outriggers were studied through experiments and finite element analyses. The test results of conventional outrigger specimen showed a steep deterioration after peak strength and an unfavorable energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Currently, high-performance concrete and steel are adopted to design and construct vertical components in super-tall buildings to improve the deformation limits corresponding to each damage stage and then alleviate the damage to the main structure under the same deformation (Nehdi, 2013;Liew et al, 2016;Hassan et al, 2017;Zhang et al, 2020). Regarding the horizontal components (e.g., coupling beam and outrigger), highperformance energy dissipation components can be introduced to dissipate plastic energy, and reduce damage to the vertical components to ensure the seismic performance of the main structure (Yang et al, 2016;Ding et al, 2018). Frame-core tube-outrigger systems, which are typical hybrid lateral loadresisting systems, and have been widely used in modern super-tall buildings (Park and Oh, 2018;Zhang et al, 2018;Shim et al, 2019;Alhaddad et al, 2020;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, high-performance concrete and steel are adopted to design and construct vertical components in super-tall buildings to improve the deformation limits corresponding to each damage stage and then alleviate the damage to the main structure under the same deformation (Nehdi, 2013;Liew et al, 2016;Hassan et al, 2017;Zhang et al, 2020). Regarding the horizontal components (e.g., coupling beam and outrigger), highperformance energy dissipation components can be introduced to dissipate plastic energy, and reduce damage to the vertical components to ensure the seismic performance of the main structure (Yang et al, 2016;Ding et al, 2018). Frame-core tube-outrigger systems, which are typical hybrid lateral loadresisting systems, and have been widely used in modern super-tall buildings (Park and Oh, 2018;Zhang et al, 2018;Shim et al, 2019;Alhaddad et al, 2020;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic characteristics of the structures equipped with outriggers were correlated from field measurement and numerical models . The seismic performances of outriggers have been experimentally studied, and the corresponding finite‐element (FE) models were validated with the experimental results . In addition, the damped‐outrigger system has achieved significant progress recently …”
Section: Introductionmentioning
confidence: 99%
“…Yang et al performed experimental and numerical studies on energy‐dissipating outriggers. Their research identified that, owing to the global buckling of the inclined braces and the local buckling of the chords, conventional outriggers have limited deformation and energy‐dissipating capacities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experimental tests have also been performed on outriggers with BRBs. Yang et al tested three 1/3‐scaled steel truss outrigger specimens: one conventional outrigger specimen and two BRB‐outrigger specimens, which used reduced beam section connections for the chords of the steel truss. The test results revealed that outriggers specimens that incorporated BRBs had superior energy dissipation capacity and ductility than the conventional outrigger specimen.…”
Section: Introductionmentioning
confidence: 99%